Restoring autonomy. Symmetry and asymmetry in care relationships - De Lange, F (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
In this article the complexity of a professional care relationship as a whole of symmetrical and asymmetrical, formal and informal dimensions, is presented. Its ethical simplicity, however, is safeguarded as long as the telos of a care relationship is seen as the restoration of the autonomy of the care receiver. Autonomy is interpreted as the capability of persons to develop their uniqueness throughout their life course. The undeniable asymmetry of the care relationship is an essential, but temporary moment in its dynamics. The dynamics of a care relationship corresponds to the heart of the Christian ethos: in the Christian narrative, the asymmetry of humiliation precedes the exaltation, understood as the restoration of human dignity as ‘living upright’. The theological concept of exaltation can be interpreted as God’s ‘care for autonomy’ in a ethics of care.